1982
DOI: 10.1111/j.1699-0463.1982.tb01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Precipitation in Counter Current Electrophoresis. A Sensitive Method for Detection of Mink Antibodies to Aleutian Disease Virus

Abstract: Inhibition of precipitation in counter current electrophoresis was at least 32 times more sensitive when compared to the normal counter current electrophoresis for the demonstration of mink antibodies against Aleutian disease virus (ADV). ADV antigen can be produced from mink organs or in cell culture. The reactivity of the two types of antigen in the two kinds of counter current electrophoresis methods is described in this report. When 22 mink sera were titrated in normal counter current electrophoresis again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The CIEP 13 test is widely used for testing mink for infection with AMDV because of its low cost, high specificity, and acceptable sensitivity. 1,3,5,17 Methods of detecting anti-AMDV antibodies with higher sensitivity than CIEP have been developed, 13,5,6,34 which could increase the chance of detecting infected animals at early periods after infection. These tests are more complex and more costly than CIEP and are not used for routine herd screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CIEP 13 test is widely used for testing mink for infection with AMDV because of its low cost, high specificity, and acceptable sensitivity. 1,3,5,17 Methods of detecting anti-AMDV antibodies with higher sensitivity than CIEP have been developed, 13,5,6,34 which could increase the chance of detecting infected animals at early periods after infection. These tests are more complex and more costly than CIEP and are not used for routine herd screening.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between the 2 sources of antigen showed that antibody titer measured by the organ-produced antigen was higher than that by the in vitro–grown antigen. 3 This change in the source of antigen could be the reason for the decrease in sensitivity of CIEP after 1983. For instance, antibodies were detected by organ-produced CIEP in 1 of the 8 inoculated mink at 7 dpi, all 4 mink at 9 dpi, and 5 of the 6 mink at 11 dpi, 16 as well as in all 19 mink tested at 7 dpi and in another 97 mink tested at 10 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…CIEP based on in vitro grown AMDV antigen (AMDV-G) has been found effective for detecting serum antibodies to AMDV [8,16], and has been referred to as a gold standard [16]. However, the method in itself is labor consuming, and interest has therefore been paid to other antibody detecting systems in order to enable automation.…”
Section: Introductionmentioning
confidence: 99%
“…CIEP was developed in the 1970s using an organ-produced antigen. In the 1980s, in vitro cultured (Crandell feline kidney cells) antigen for AMDV-G strain was widely utilized [17]. Although CIEP is highly specific, it has poor sensitivity, is time-consuming and requires large quantities of antigen.…”
Section: Introductionmentioning
confidence: 99%